(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Covid-19, which was defined as a result of research conducted in a group of patients developing respiratory symptoms in late December 2019 in Wuhan province of China, spread to other countries in a very short time by infecting from people to people. On January 30, 2020, the World Health Organization declared the “International Public Health Emergency” due to the Covid-19 pandemic. Travel restrictions have been imposed by countries to prevent the pandemic. With these restrictions, air traffic has come to a halt, only health, humanitarian, military, repatriation and cargo flights have been carried out. Due to the Covid-19, more than 6 million traffic losses occurred in the European air traffic network. There were 0.2 million flight losses in the 9/11 attacks and 0.8 million flight losses in the great financial crisis. It is not known how long the recovery will take to reach traffic data in 2019. In this study, the impact of Covid-19 on the European and Turkey air traffic networks in 2020 was analyzed compared to the 2019 data. Within the scope of forecasts published by aviation authorities, assessments regarding the recovery process are also included. It is predicted that the impact of the Covid-19 pandemic on the air traffic networks will not be compensated for a long time in line with current data and predictions for the pandemic.